INVESTIGATION OF ROTAVIRUS INFECTION IN COW CALVES AND ASSOCIATED RISK FACTORS WITH HAEMATO-BIOCHEMICAL ALTERATIONS - SAFDAR ABBAS; Dr. Jawaria Ali Khan; Dr. Syed Saleem Ahmed; Prof. Dr. Aftab Ahmed Anjum (Journal of Animal and Plant Sciences, 2023)
The bovine rotavirus (BRoV) is one of the major causes of illness and death in newborn calves. The study's objective was to pinpoint the haemato-biochemical alterations, other risk factors, and molecular manifestations associated with BRoV infections in dairy cow calves in in Jhelumdistrict, Pakistan. From July 2020 to June 2021, a total of 200 faeces samples were taken from neonate cow calves under 28 days old that had a history of diarrhea and dysentery. Prior to further polymerase chain reaction processing, samples were initially screened using S&C Biotech Bovine Rotavirus Antigen Rapid Test Kits. For the haemato-biochemical study, blood samples were obtained from calves infected with BRoV. On a questionnaire form, information was gathered for the analysis of the various risk factors linked to the occurrence of BRoV infection. The occurrence of BRoV infection while utilizing diagnostic screening kits was 26% (52/200), and when using RT-PCR, it was 21.5% (43/200). BRoV infection was significantly (p<0.05) influenced by breed, age, sex, vomiting, prior history of diarrhea, bodily conditions, food type, colostrum feeding, deworming history, living environment, interaction with other animals, and season. Hematological and biochemical markers showed significant (p<0.05) alterations. Mean corpuscular volume, basophils and lymphocytes were decreased significantly (p<0.05 while mean corpuscular hemoglobin, total leukocyte count, TEC, white blood cells count, red blood cell and Monocytes were increased significantly (p<0.05). Similarly, among biochemical parameters, Potassium was non-significantly (p>0.05) increased, while Sodium, Calcium, copper and iron were significantly (p<0.000) decreased. It was concluded that assumed risk factors were contributed to the BRoV infection, and infected calves showed haemato-biochemical changes.
Keywords: neonatecalves; rotavirus; diagnostic test; Pakistan